Dependence of anuran diversity on environmental descriptors in farmland ponds - da Silva, Fernando Rodrigues; Candeira, Carolina Panin; Rossa-Feres, Denise de Cerqueira [UNESP] (Springer, 2012)
In the Neotropics, conversion of natural habitats into agricultural areas is occurring at a high rate, with consequent reduction of habitat complexity in anuran breeding ponds. Identifying features of farmland ponds that allow them to support a high diversity of species is fundamental for successful management and conservation policies and is especially important in Neotropical regions that harbor the highest anuran species richness in the world. Here, we aimed to investigate which environmental descriptors correlate the occurrence of anuran species in tropical farmland ponds in southeastern Brazil. We found that environmental descriptors reflecting the complexity of vegetation in farmland ponds primarily predict the diversity of anuran species in these habitats. Species richness was correlated mainly by vegetation height in the margin, with ponds that exhibit greater stratification harboring a larger number of species. Vegetation height in the interior of ponds, diversity of vegetation in the margin, pond area and hydroperiod were also important variables predicting the abundance of six of 10 anuran species analyzed. Our results show that features of farmland ponds representing increased habitat complexity are key factors in maintaining a high diversity of species, providing a greater variety of microhabitats, both in vertical and horizontal strata, and thus meeting diverse species-specific requirements.
Keywords: Amphibian; Generalized linear models; Hierarchical partition; Heterogeneity; Mesophytic semideciduous forest